2017
DOI: 10.19173/irrodl.v18i5.2751
|View full text |Cite
|
Sign up to set email alerts
|

Massive, Open, Online, and National? A Study of How National Governments and Institutions Shape the Development of MOOCs

Abstract: We explore interpretations of MOOCs around the globe and, in particular, interpretations of MOOCs in Norway. Based on a review of previous studies relevant to these topics, we present two contrasting views on the emergence and development of MOOCs, namely the global interruption view and the national mediation view. We suggest, based on previous studies that MOOCs seem to follow national paths more than global paths. In order to grasp the diversity of understandings of MOOCs, we developed a framework that embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…MOOCs include various technologies and ways of organization. Research has demonstrated that countries around the world adjust and interpret MOOCs to fit their educational systems, technological infrastructure, and their cultural and economic system (Tømte, Fevolden, & Aanstad, 2017).…”
Section: Moocs As Professional Development Programmentioning
confidence: 99%
“…MOOCs include various technologies and ways of organization. Research has demonstrated that countries around the world adjust and interpret MOOCs to fit their educational systems, technological infrastructure, and their cultural and economic system (Tømte, Fevolden, & Aanstad, 2017).…”
Section: Moocs As Professional Development Programmentioning
confidence: 99%
“…For example, via MOOCs, we can study the scope and degree of involvement of technology providers in the sector, the changes these relationships bring to traditional learning, and how HEIs are transforming as organisations. Various MOOC conceptualisations have emerged around the world and are often adapted to specific local cultural, political, and economic circumstances (Tømte et al, 2017;Shah, 2019). The variety of practices and understandings surrounding MOOCs reflects the capabilities and limitations of countries' technological infrastructures, their historical trajectories and natures, and a profile of their respective HE systems and providers.…”
Section: Setting the Scene: Digital Transformation In He And Moocsmentioning
confidence: 99%
“…We propose a typology of MOOCs, including two initial main categories, namely 'motivation' and 'content' (Tømte et al, 2017). 'Content' includes various target groups and types of accreditation, such as heterogeneous groups of students in terms of geography, occupation, and education.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In a review of previous studies, Tømte, Fevolden & Aanstad (2017) have found two contrasting views on the emergence and development of MOOCs: "the global disruption view and national mediation view" (p. 211). The proponents of the first view see the MOOCs as innovation and competition drivers for HE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A government appointed commission for investigating the possibilities for adopting MOOCs into Norwegian higher education system found that the pace of digitalisation of HE in Norway has been slow and argues that MOOCs and new digital technologies can help develop Norwegian knowledge society. The main motivations for adopting MOOCs in Norwegian HE context are for strengthening quality, access, and marketing of Norwegian education and research, increase recruitment and cooperation, and reduce costs (Tømte et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%